2020
DOI: 10.3389/fneur.2020.583368
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Feasibility, Adherence, and Appreciation of a Newly Developed Tele-Rehabilitation Program for People With MCI and VCI

Abstract: Background: Patients with Mild Cognitive Impairment (MCI) and Vascular Cognitive Impairment (VCI) are at a high risk of progressing to dementia. Recent guidelines indicate the importance of promoting multidimensional and multi-domain interventions to prevent further decline. Due to its growing effectiveness, comparable to conventional face-to-face interventions, the use of technology is gaining relevance. Tele-rehabilitation systems have the potential to engage patients in multi-dimensional activity programs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 57 publications
6
45
0
6
Order By: Relevance
“…A total of 9% (n=3) of studies used a mixed methods methodology [ 3 , 87 , 96 ], whereas the remaining studies (28/34, 82%) used a quantitative methodological approach. Of the 28 quantitative studies, 8 (n=8, 28%) used a randomized controlled trial design [ 89 , 90 , 97 , 101 , 106 , 107 , 109 , 110 ]. Other quantitative studies have used observational or nonrandomized trial designs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 9% (n=3) of studies used a mixed methods methodology [ 3 , 87 , 96 ], whereas the remaining studies (28/34, 82%) used a quantitative methodological approach. Of the 28 quantitative studies, 8 (n=8, 28%) used a randomized controlled trial design [ 89 , 90 , 97 , 101 , 106 , 107 , 109 , 110 ]. Other quantitative studies have used observational or nonrandomized trial designs.…”
Section: Resultsmentioning
confidence: 99%
“…The focus of digital health interventions varied. For example, some were related to medication reconciliation [ 79 , 81 , 97 , 104 ], whereas others aimed at providing education (eg, about rehabilitative exercises), internet-based care, and resources [ 83 , 86 , 89 , 92 , 94 , 96 , 100 , 104 - 106 , 111 ] and improved communication and care coordination with older adults’ care providers [ 3 , 82 , 91 , 104 , 108 ]. A total of 2 interventions aimed to improve communication processes among health care providers regarding discharge processes and care plans [ 93 , 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, participants in the control group who received conventional behavioral change via face-to-face were reported giving burden to the caregivers [ 42 ]. Another study revealed that ICT platforms used to conduct telerehabilitation was suitable to be implemented among MCI patients as drop-out rate in the control group was higher when compared to telerehabilitation intervention group [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other protocol randomized controlled studies with multi-domain of telerehabilitation intervention were also outlined to conduct the same goal which is to counteract cognitive dysfunction and enhance quality of life such as Games for Older Adults Active Life (GOAL) Project and TV-AssistDem [ 65 , 91 ]. Telerehabilitation was found to be feasible among people with mild cognitive impairment or vascular cognitive impairment [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…daily steps [57]), and improving self-efficacy in diabetic patients [23,59]. One telerehabilitation study for individuals with MCI, GOAL (Games for Older Adults' Active Live) Project [13] uses an 8-week app-based program to complete cognitive (computerized training), physical (guided videos of exercises), and caregiver training [37]. Although the program has demonstrated good attendance and low attrition rates, its efficacy has not yet been established with regard to allaying cognitive decline or improving mood or other outcomes.…”
Section: Health Informatics and Telehealthmentioning
confidence: 99%